2023
DOI: 10.1111/jcmm.17985
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of cuproptosis and Cu metabolism‐associated genes to chronic obstructive pulmonary disease

Wenchuan Qi,
Lu Liu,
Qian Zeng
et al.

Abstract: Airway epithelial cell injury plays a crucial role in the pathogenesis of chronic obstructive pulmonary disease (COPD). However, a novel form of Cu‐induced programmed cell death known as cuproptosis has not yet been thoroughly investigated in the context of COPD. Clinical reports have suggested that high copper exposure may increase the risk of COPD. In this study, we aimed to determine the expression and potential functions of cuproptosis‐related genes and genes associated with copper metabolism in COPD. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Qi et al found that 18 key Cu metabolization-related genes were significantly enriched in signaling pathways and biological processes associated with COPD development. DLD and CDKN2A are abnormally expressed in the airway epithelial cells of patients with COPD, and smoking can promote their expression to a certain extent, which has been verified in murine models of COPD (Qi et al, 2023). These findings suggest that the occurrence of COPD is related to the expression of Cu-regulatory genes.…”
Section: Copdmentioning
confidence: 62%
See 1 more Smart Citation
“…Qi et al found that 18 key Cu metabolization-related genes were significantly enriched in signaling pathways and biological processes associated with COPD development. DLD and CDKN2A are abnormally expressed in the airway epithelial cells of patients with COPD, and smoking can promote their expression to a certain extent, which has been verified in murine models of COPD (Qi et al, 2023). These findings suggest that the occurrence of COPD is related to the expression of Cu-regulatory genes.…”
Section: Copdmentioning
confidence: 62%
“…The exhaled breath condensate (EBC) of patients with stable COPD had lower Cu levels than those of the controls, and Cu levels in the EBC were positively related to FEV1 in subjects with COPD (Mutti et al, 2006). Elevated Cu levels have also been found in the lungs of rats with COPD (Qi et al, 2023). Cu deficiency induces emphysema in animal models (Mizuno et al, 2012).…”
Section: Copdmentioning
confidence: 99%
“…Our study focus on the differential expression of 52 genes associated with cuproptosis and Cu metabolism 22 between IPF and control groups (Figure 2A). In the IPF group (Figure 2B), a total of 14 DEGs were identified.…”
Section: Resultsmentioning
confidence: 99%
“…The study revealed a linear positive correlation between Cu levels and COPD mortality risk [34] . Qi W et al identi ed that apoptosis induced by Cu is a signi cant contributor to the development of COPD [20] . In the study, researchers established a COPD rat model and identi ed key regulators of copper-induced apoptosis (cuproptosis), primarily DLD and CDKN2A.…”
Section: Discussionmentioning
confidence: 99%
“…Research indicates that patients' serum Cu levels rise with increasing clinical severity of COPD exacerbations, suggesting they could serve as a marker for the condition's clinical deterioration [19] . A study revealed that 18 copper metabolism genes, including 5 linked to cuproptosis, play a signi cant role in COPD development through key signaling pathways and biological processes [20] . In humans, Se is integrated into selenoproteins in the form of selenocysteine.…”
Section: Introductionmentioning
confidence: 99%